Strategic exploitation of fluctuating asymmetry in male Endler's guppy courtship displays is modulated by social environment - Řežucha, R; Reichard, M (Journal of evolutionary biology, 2015)
Lateral asymmetry in signalling traits enables males to strategically exploit their best side. In many animals, both body colouration and fluctuating asymmetry are signals of male attractiveness. We demonstrated experimentally that even sexually naïve male Poecilia wingei were able to identify their most attractive side (i.e. that with a higher proportion of carotenoid pigmentation) and use it preferentially during courtship. Notably, males retained their strategic signalling in a male-biased social environment, whereas they ceased to signal strategically in a female-biased environment. The degree of asymmetry in colouration did not affect overall courtship activity. Strategic lateralization in courtship displays was strongest and most repeatable in the male-biased social environment where males competed with rivals for matings. Individual asymmetry in colouration changed considerably over a period of 3 months. This suggests that colouration is a dynamic feature during adulthood and that males are capable of tracking and strategically exploiting their lateral asymmetry in accordance with their social environment.
Keywords: social environment; Poecilia wingei; Sexual Behavior, Animal; Social Behavior; behavioural laterality; Models, Biological; Male; experience; ženské pohlaví; biologické modely; Poecilia; Carotenoids; Animals; zvířata; sigmoid display; sociální chování; mužské pohlaví; sexuální chování zvířat; karotenoidy; sidedness; Female; živorodka